Elucidating the Structural Chemistry of a Hysteretic Iron(II) Spin‐Crossover Compound From its Copper(II) and Zinc(II) Congeners. Issue 21 (30th March 2020) - Pask, Christopher M.; Greatorex, Sam; Kulmaczewski, Rafal; Baldansuren, Amgalanbaatar; McInnes, Eric J. L.; Bamiduro, Faith; Yamada, Mihoko; Yoshinari, Nobuto; Konno, Takumi; Halcrow, Malcolm A.
Abstract: Annealing [Fe L 2 ][BF4 ]2 ⋅ 2 H2 O ( L= 2, 6‐ bis ‐[5‐methyl‐1 H ‐pyrazol‐3‐yl]pyridine) affords an anhydrous material, which undergoes a spin transition at T 1/2 =205 K with a 65 K thermal hysteresis loop. This occurs through a sequence of phase changes, which were monitored by powder diffraction in an earlier study. [Cu L 2 ][BF4 ]2 ⋅ 2 H2 O and [Zn L 2 ][BF4 ]2 ⋅ 2 H2 O are not perfectly isostructural but, unlike the iron compound, they undergo single‐crystal‐to‐single‐crystal dehydration upon annealing. All the annealed compounds initially adopt the same tetragonal phase but undergo a phase change near room temperature upon re‐cooling. The low‐temperature phase of [Cu L 2 ][BF4 ]2 involves ordering of its Jahn–Teller distortion, to a monoclinic lattice with three unique cation sites. The zinc compound adopts a different, triclinic low‐temperature phase with significant twisting of its coordination sphere, which unexpectedly becomes more pronounced as the crystal is cooled. Synchrotron powder diffraction data confirm that the structural changes in the anhydrous zinc complex are reproduced in the high‐spin iron compound, before the onset of spin‐crossover. This will contribute to the wide hysteresis in the spin transition of the iron complex. EPR spectra of copper‐doped [Fe0.97 Cu0.03 L 2 ][BF4 ]2 imply its low‐spin phase contains two distinct cation environments in a 2:1 ratio. Abstract : In a spin : Structurally different [M L 2 ][BF4 ]2 ⋅ 2 H2 O ( L= 2, 6‐ bis [5‐methyl‐1 H ‐pyrazol‐3‐yl]‐pyridine; M=Fe, Cu or Zn) form the same anhydrous phase on annealing, which transforms to one of two new phases near room temperature. [Zn L 2 ][BF4 ]2 shows unusual structural changes between 285–150 K, which are duplicated in its iron analogue by powder diffraction. This will contribute to the previously reported 65 K thermal hysteresis in the spin‐transition shown by [Fe L 2 ][BF4 ]2 .